Prevention of Fraud by the Role of Bintibsos through Counseling Guidance in West Lombok Police Area - Nova Pamungkas (Advances in Police Science Research Journal, 2022)
This research is motivated by the high number of fraud cases that can be troubling to the public, causing disturbances in public order and security in the West Lombok Regency area. The police as protectors, protectors, and public servants try to maintain public order through preemptive efforts, namely through counseling guidance. The role of bimluh, hereinafter referred to as counseling guidance, is very important in preventing criminal acts of fraud. This study aims to describe the description of the criminal act of fraud, explain the role of the Bintibsos unit through Bimluh in preventing criminal acts of fraud and describe the factors that influence the role of the Bintibsos unit through Bimluh in preventing fraud in the area of ​​the West Lombok Police. these are Role Theory, Management Theory, Crime Prevention Theory. Furthermore, the concepts used are Role Concepts, Counseling Guidance, Fraud Crimes. This research was conducted using a qualitative approach with field research methods. Data were collected through interviews, observations, and document studies, as well as data validity using data triangulation. The results of the study found that the fraud case was the most prominent case in the West Lombok Police Law area. The role of the Bintibsos Unit through Bimluh in preventing fraudulent acts is not optimal where there are points that cannot be implemented, namely at the point of compiling a team of activity organizers and in practice not carrying out the function of leadership and motivation. Then based on the type of crime prevention carried out only secondary prevention is carried out in its implementation. Then in this study found factors that influence the role of the social and social welfare unit through counseling guidance in preventing criminal acts of fraud internally and externally.